Tanaka and Cycling Test of Water Pumpkin Fruit Extract (Lagenaria siceraria (Molina) Standl.) as Natural Hair Tonic Spray - Sofya, Sri Winarni; Muhsin, Lalu Busyairi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Hair loss and slow hair growth remain common cosmetic concerns, while prolonged use of synthetic hair growth agents may pose safety and sustainability issues. This study aimed to investigate the effectiveness and stability of a natural hair tonic spray formulated from water pumpkin (Lagenaria siceraria (Molina) Standl.) fruit extract. The extract was prepared using ethanol maceration and incorporated into three formulations with concentrations of 5%, 10%, and 15%. Effectiveness was assessed through a Tanaka hair growth test on rabbits for 21 days, while stability was evaluated through a 28-day cycling test, involving alternating temperature cycles (2–8°C, 25°C, and 40°C). The results indicated that all formulations exhibited stable organoleptic characteristics, pH, and homogeneity throughout storage. The F3 formula (15%) demonstrated the highest hair growth activity (2.4 cm average length), comparable to the positive control (2.7 cm). The enhanced hair growth effect is attributed to flavonoids and saponins that improve microcirculation around follicles and stimulate keratinocyte proliferation. This research highlights the potential of water pumpkin fruit extract as a sustainable and cost-effective natural alternative to synthetic hair growth agents. Future studies should explore optimization of formulation stability and molecular mechanisms underlying follicular activation.